2016
DOI: 10.1136/bmjstel-2015-000097
|View full text |Cite
|
Sign up to set email alerts
|

Stress and anxiety management strategies in health professions' simulation training: a review of the literature

Abstract: IntroductionSimulation training has been used to teach clinical skills to health profession trainees. Stress and/or anxiety occur in high-acuity scenarios in the clinical environment, and affect clinician performance and patient outcomes. To date, strategies that have been used in conjunction with simulation training for healthcare professionals that address stress management are limited. This paper reports a literature review conducted to explore strategies used with simulations to enhance the ability of heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 37 publications
0
20
0
Order By: Relevance
“…The literature suggests that medical staff treating patients with COVID-19 report high levels of anxiety and low self-efficacy levels [39,40], and other research on Wuhan healthcare workers reported great vulnerability to stress, anxiety, and depression, suggesting that frontline healthcare workers should be closely monitored as a high-risk group for maladjustment [29]. Excessive stress and/or anxiety in the clinical context may affect performance and can compromise patient outcomes [41].…”
Section: Discussionmentioning
confidence: 99%
“…The literature suggests that medical staff treating patients with COVID-19 report high levels of anxiety and low self-efficacy levels [39,40], and other research on Wuhan healthcare workers reported great vulnerability to stress, anxiety, and depression, suggesting that frontline healthcare workers should be closely monitored as a high-risk group for maladjustment [29]. Excessive stress and/or anxiety in the clinical context may affect performance and can compromise patient outcomes [41].…”
Section: Discussionmentioning
confidence: 99%
“…There are many theories on physical processes and external types of stressors. These may be categorized in two ways: "systemic" stress these are based on psychobiology, and physiology [11] and mental stress developed within the field of cognitive psychology [1][2][3][4][5][6][7][8][9][10][11][12][13][14].…”
Section: Theories On Stressmentioning
confidence: 99%
“…Programs used with simulations to enhance the coping skills of health profession trainees in reducing stress and anxiety have shown increased levels of effectiveness during high anxiety clinical situations [9]. Effectiveness of a theory-based online intervention to help undergraduate students cope with the stress management has shown shows positive results [10].…”
Section: Introductionmentioning
confidence: 99%
“…By being encouraged to voice concerns during an emergency, trainees can act as partners in the reduction of possible medical errors. Further, in a literature review by Ignacio et al, it was found that "excessive stress and/or anxiety in the clinical setting have been shown to affect performance and could compromise patient outcomes [22]." In and out of the field of medicine, studies have "suggested that stress training showed an improving trend in performance….…”
Section: Idea and Innovationmentioning
confidence: 99%
“…[and was a] valuable strategy for enhancing… thought process and improving… performance in communication skills [22]." By presenting the junior residents with a stressful situation in which an attending suggests a management option that might not be appropriate for the patient, the residents learn how to properly and respectfully suggest an alternate treatment approach, while also learning the technical skills needed to properly care for such a patient.…”
Section: Idea and Innovationmentioning
confidence: 99%